Gender and Emotional Maturity Categories Among Students at SMP Negeri 1 Pakis: Implications for Gender-Responsive Guidance and Counseling Services - Anisa Safitri; Henny Indreswari; M Ramli; Khairul Bariyyah (UIN Siber Syekh Nurjati Cirebon, 2026)
Emotional maturity is an important developmental competence that supports adolescents in regulating emotions, building healthy interpersonal relationships, and responding adaptively to developmental demands. This study aimed to examine the association between gender and emotional maturity categories among students at SMP Negeri 1 Pakis and to identify its implications for gender-responsive Guidance and Counseling services. A quantitative cross-sectional comparative design was employed involving 134 students, consisting of 67 male and 67 female students aged 12–15 years. Data were collected using a 25-item emotional maturity scale adapted from Hilyana (2020), covering self-awareness, self-regulation, motivation, empathy, and social skills. The instrument demonstrated excellent internal consistency, with McDonald’s ω = .933. Data were analyzed using descriptive statistics and the Fisher–Freeman–Halton exact test, while Cramér’s V was used to estimate the effect size. The results showed that 91.0% of students were classified in the moderate emotional maturity category, 5.2% in the low category, and 3.7% in the high category. Although female students showed a higher proportion in the high category than male students, no statistically significant association was found between gender and emotional maturity category, p = .350, with a small effect size, Cramér’s V = .124. These findings indicate that gender should not be used as the sole basis for evaluating students’ emotional development. Guidance and Counseling services should therefore be universal, inclusive, and gender-responsive, while remaining grounded in students’ actual developmental needs rather than gender stereotypes.